Peningkatan Motivasi dan Hasil Belajar Melalui Implementasi Model STAD Pada Mata Pelajaran PKn Kelas IV SD 5 Bae Kabupaten Kudus Tahun Ajaran 2014/2015 - Chris Purwati; Muhammad Akhyar; Siti Sutarmi Fadhilah (Teknodika, 2017)
The objectives of this research are: (1) to improve of the learning motivation in civics education subject matter of the students in grade IV of primary school 5 of Bae, Kudus regency in academic year 2014/2015; and (2) to improve the learning achievement in civics education subject matter of the students in grade iv of primary school 5 of Bae, Kudus regency in academic year 2014/2015. This research used the classroom action research with two cycles. Each cycle consisted of four phases, namely: Planning, Implementation, Observation, and Reflection. The subjects of research were the students in grade IV of the school. The data of research were collected through observation, documentation, in-depth interview, and test of learning achievement. They were analyzed by using the descriptive model o analysis. The results of research are as follows: 1) The STAD learning model can improve the learning motivation in Civics Education subject matter of the students in Grade IV of Primary School 5 of Bae, Kudus Regency in Academic Year 2014/2015. It trains the students to deliver their opinions and to have cooperation or teamwork in their own team. Prior to the treatment (Pre-cycle), their learning motivation was 53.99%. After the treatment, it became 65.22% in cycle I and 82.61% in cycle II respectively. 2) The STAD learning model can also improve the learning achievement in Civics Education subject matter of the students in Grade IV of Primary School 5 of Bae, Kudus Regency in Academic Year 2014/2015. Prior to the treatment, the percentage of the students’ learning completeness was 26.09%. After the treatment, it became 56.52% in Cycle I and95.65% in Cycle II respectively.